Supporting strategic cultural change: the Strathclyde Learning Technology Initiative as a model - Allison Littlejohn; Shona Cameron (Association for Learning Technology, 1999)
Higher education is in a period of great cultural change, accelerated by government recommendations (e.g. the Dearing Report), the introduction of tuition fees, implications arising from the National Grid for Learning and changes within secondary education (DfEE, 1997). More demands are being made on students to become independent, reflective learners. Much of this is coming from potential employers who are also requiring graduates to develop other personal transferable skills such as communication via new technologies (Harvey, Moon and Geal, 1997).